2006
DOI: 10.1089/oli.2006.16.337
|View full text |Cite
|
Sign up to set email alerts
|

2´-Deoxy Purine, 2´-O-Methyl Pyrimidine (dRmY) Aptamers as Candidate Therapeutics

Abstract: Aptamers are short oligonucleotides that fold into well-defined three-dimensional architectures thereby enabling specific binding to molecular targets such as proteins. To be successful as a novel therapeutic modality, it is important for aptamers to not only bind their targets with high specificity and affinity, but also to exhibit favorable properties with respect to in vivo stability, cost-effective synthesis, and tolerability (i.e., safety). We describe methods for generating aptamers comprising 2 - deoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…146 With the same approach, aptamers to multiple target proteins, including interleukin (IL)-23 and thrombin, have been successfully isolated. 147 Another aptamer that may be useful in hematology is a 15-nucleotide, G-quadruplex-forming DNA aptamer that efficiently blocks the proteolytic activity of thrombin, a serine protease involved in thrombosis and hemeostasis. 15,148 The anti-thrombin aptamer was one of the first aptamers tested in animal studies in the early 1990s.…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…146 With the same approach, aptamers to multiple target proteins, including interleukin (IL)-23 and thrombin, have been successfully isolated. 147 Another aptamer that may be useful in hematology is a 15-nucleotide, G-quadruplex-forming DNA aptamer that efficiently blocks the proteolytic activity of thrombin, a serine protease involved in thrombosis and hemeostasis. 15,148 The anti-thrombin aptamer was one of the first aptamers tested in animal studies in the early 1990s.…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…This enzyme is also able to polymerize transcripts containing 4 -thiopyrimidines ( Figure 1.2a), a modification that increases their stability by about 50-fold relative to unmodified RNA (Kato et al, 2005). It was recently reported that the combination of mutated T7 RNA polymerases, Y639F and Y639F/H784A, allows the efficient incorporation of all four 2 -O-methyl nucleotides (Chelliserrykattil and Ellington, 2004;Burmeister et al, 2005Burmeister et al, , 2006. The positions that remain unmodified at the end of the in vitro selection procedure (e.g., the purine residues in a selection carried out with 2 -fluoropyrimidine triphosphates) can be modified post-SELEX for further optimization of the aptamers.…”
Section: The Chemistry Drives the Shapementioning
confidence: 97%
“…126 Stemming from their initial enzymatic recognition studies, 2 0 -amino pyrimidines, 2 0 -fluoro pyrimidines and 2 0 -O-Methyl nucleotides have been successfully applied in aptamer development by conventional SELEX-based methodologies. [127][128][129][130][131][132][133][134] LNA is one of the successful nucleotide analogs extensively utilized in various fields because of their remarkable properties. 113,114 In LNA the sugar ring is conformationally locked by a O2 0 -C4 0 methylene linkage to adopt N-type sugar puckering.…”
Section: Chemically Modified Aptamer-oligonucleotide Chimeramentioning
confidence: 99%